2016
DOI: 10.1177/1087054716664413
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Cognitive Behavioral Therapy for Adults With ADHD: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Objective: To systematically review published RCTs of cognitive behavioural therapy (CBT) for adult ADHD and establish the effectiveness of CBT reducing ADHD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 45 publications
(110 reference statements)
1
48
0
2
Order By: Relevance
“…Adult ADHD should be treated if the impairment is moderate to severe (severe psychosocial impairment is present in approximately 30% of affected individuals [12]) (18), using both pharmacotherapy and behavioral therapy. Moderate to large effect sizes (0.6 to 4.3) are reported for stimulant pharmacotherapy, while data on the efficacy of psychotherapeutic interventions is divergent (19,20). Treatment response (at least 30% reduction in symptoms) is approximately 60% if medication is administered according to guidelines (21,22).…”
mentioning
confidence: 99%
“…Adult ADHD should be treated if the impairment is moderate to severe (severe psychosocial impairment is present in approximately 30% of affected individuals [12]) (18), using both pharmacotherapy and behavioral therapy. Moderate to large effect sizes (0.6 to 4.3) are reported for stimulant pharmacotherapy, while data on the efficacy of psychotherapeutic interventions is divergent (19,20). Treatment response (at least 30% reduction in symptoms) is approximately 60% if medication is administered according to guidelines (21,22).…”
mentioning
confidence: 99%
“…Die kognitive Verhaltenstherapie, die die Therapie dysfunktionaler Kognitionen zur Behandlung der ADHS im Erwachsenenalter betont, wurde bislang am häufigsten in Studien untersucht -mit Wirksamkeitsnachweisen sowohl im Einzel-als auch im Gruppensetting [27]. Sie wird aktuell als der effektivste psychotherapeutische Ansatz zur Reduktion der ADHS-Symptomatik sowie zur Symptomenlinderung von komorbiden Störungen (z.…”
Section: Psychotherapeutische Interventionenunclassified
“…CBT has been shown to be superior over wait list controls and active controls (alternative treatment to CBT) in reducing ADHD symptoms immediately post treatment. 33 Coaching ADHD coaches specialize in working with individuals with deficits in executive functioning and organization skills. 35 ADHD coaching has become increasingly popular in recent years, particularly as a treatment option for college students.…”
Section: Antidepressant and Anticonvulsant Medicationmentioning
confidence: 99%
“…One of the most widely recommended psychosocial treatments for ADHD is cognitive-behavior therapy (CBT), a goaloriented form of psychotherapy that generally aims to replace maladaptive patterns of thoughts and behaviors with more adaptive thoughts and behaviors. 33 Several studies have shown CBT to be effective at reducing the severity and frequency of adverse symptoms of ADHD as a primary treatment and/or in combination with psychopharmacology. 34 In addition to CBT, individual counseling, group treatment, vocational counseling, coaching, the use of assistive technology, stress reduction strategies, anger management, and promotion of self-care may also help individuals to reduce or manage their ADHD symptoms.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
See 1 more Smart Citation